The Theory of Instant Prohibition of Drinking Wine from the Perspective of the Holy Book of Quran and Narrations (Arabic: رِوایات) - Yaqub Barzegar Shani; Sayyid Muhammad Naqib; Mahdi Davari (آموزه‌های قرآنی, 2023)
The intellect is the distinguishing feature of man from animals which has not been found anything more harmful than wine for intellect and the descent of man into the position of animalism is the result of that. Wine has always been forbidden in the heavenly religions based on this, however, the time and manner of declaring its prohibition in Islam has led to the confrontation of two viewpoints in the instant prohibition with the intoxicate of sleep in the sense of the state of being intoxicated (Arabic: سُکارَی) in verse 4:43 An-Nisāʾ (Arabic: النساء, An-Nisāʾ) and gradual prohibition with the intoxicate of wine. The findings of this research by a library study and descriptive analytical method indicate the accuracy of the theory of instant prohibition with Quranic, narrational proofs and rational confirmations and historical evidence in declaring the prohibition of wine in Makkī (Arabic: المکّیّ, suras revealed in Mecca) verses in early Biʿtha (Arabic: بِعثة) and its emphasizing in verse 5:90 Al-Maʾidah (Arabic: المائدة, Al-Māʾidah). In contrast, the inaccuracy of the theory of gradual prohibition of wine was proved due to its content contradiction and opposition to the Holy Book of Quran, because it is stated, on the one hand, that wine in the first stage was forbidden during the prayer time with the revelation of verse 43 of An-Nisāʾ, the sixth Madanī (Arabic: المدنیّ, suras revealed in Medina) surah in order to justify the gradual theory with the gradual rational law, but on the other hand, it is stated to the absolute prohibition of wine in its verse 219 and also in some Makkī verses by violating the law of gradualness, by declaring that Surah Al-Baqarah is one of the first Madanī Chapters (suras) according to consensus that was revealed after the Hijrah (Arabic: الهجرة). Consequently, the occasions or circumstances of revelations in Sunni exegeses by negation the intoxication of wine in gradual theory have subjective exit from this verse for the motivation of defense of drinking wine of some people and the unjust attribution to others by incorrect justifying the allowance of wine until the revelation of verse 43 of An-Nisāʾ in Medina. Therefore, the distinction between declaring the prohibition of wine in Mecca in early Biʿtha and the delay of several years of execution of Ḥadd (fixed punishment) of Khmer (the drinking of alcohol, shurb khamr) in Medina in instant theory, in addition to creating strong motivation in leaving and religious final notice has also been a kind of educational method of Islam. While the announcement of the absolute prohibition of wine at the same time as the implementation of its Ḥadd (fixed punishment) with the revelation of verse 90 of Al-Maʾidah from the last Madanī Surahs (Surah Madaniyah) or Madani chapters in the gradual theory is against the educational method expected by them. The unjustifiable consumption of some companions of drinking wine in Medina until the revelation of the prohibition verse in addition to the achievement of the Quranic theory of Saib Tabrizi (Persian: صائب تبریزی, Romanized: Ṣāʾib Tabrīzī) is among the consequences of proving instant theory of the prohibition wine.